Breaking the Bounds of Slavery The Legacy of the Voting Rights Act of 1965 - Mechouar, Nessrine (My University, 2020)
The American Civil War of 1861 marked a turning point in the history of the USA bringing many changes, more particularly, to the state of African Americans by liberating them from the bonds of slavery. However, despite the Emancipation Proclamation act Blacks, actually unchained, were to witness segregation, racism and bad treatments. In other words, African-Americans were not treated as a citizen and were deprived from the majority of rights. One of the most important forms of protest aiming at bringing more equality and freedom was the Civil Rights Movement of 1960s. An attempt to improve black people’s life conditions and eradicate racism. Between 1954 and 1968, there was a passage of –at least-four major Civil Rights Acts thanks to the efforts made by the movement’s marches, activities and demonstrations: the 1964 Civil Rights Act, the 1965 Voting Rights Act, the 1965 Elementary and Secondary Education Act and the 1968 Housing Act. Each piece of legislation aimed to address racial problems during the time. These acts advanced the most important goal of the movement which is the improvement of black’s rights opportunities. Hence, this research focuses on the examination of the ultimate effectiveness of the legislation, which is one of a matter of degree. It aims to enhance in particular the role of acts that called for voting. The right to vote was so important in the sense that it could be achieved and unthreatened; African Americans would have the ability to productively create change. This research evaluates a question of whether the 1965Voting Rights Act provided African-Americans with an undeterred vote or not, by using participation rates, registration and data on black congressional representations.
Keywords: Civil Rights Movement; Martin Luther King Jr; Civil War; Reconstruction; Voting Rights Act; Selma March